Dedicated cautery-enhanced tubular self-expandable metal stent for endoscopic ultrasound-guided hepaticogastrostomy: feasibility study - Vargas-Madrigal, Jorge; Chan, Shannon M.; Dhar, Jahnvi; Teoh, Anthony Y.B.; Samanta, Jayanta; Lakhtakia, Sundeep; Giovannini, Marc (Endoscopy, 2024)
Background Endoscopic ultrasound-guided hepaticogastrostomy (EUS-HGS) is an alternative for biliary drainage in patients with obstructive pancreaticobiliary pathology when endoscopic retrograde cholangiopancreatography (ERCP) is not feasible. Despite its effectiveness, EUS-HGS is associated with a significant risk of adverse events. This study aimed to evaluate the feasibility and safety of a newly designed dedicated cautery-enhanced tubular self-expandable metal stent (SEMS) for EUS-HGS.Methods This multicenter prospective study included patients with malignant biliary obstruction in whom ERCP had failed because of tumor infiltration, inability to drain the intrahepatic ducts, or surgically altered anatomy. A dedicated cautery-enhanced tubular SEMS was used for EUS-HGS. Technical and clinical success rates, procedure times, and adverse events were evaluated.Results 20 patients underwent EUS-HGS with the dedicated stent. Technical and clinical success rates of 100% were achieved, with no reported severe adverse events or mortality. The median procedure time was 16 minutes. Recurrent biliary obstruction was observed in 1 patient.Conclusions The dedicated cautery-enhanced tubular SEMS for EUS-HGS can simplify the procedure and enhance its safety and efficacy. This innovation shows promise for improving patient outcomes, although further studies are needed to validate these findings in a broader patient population.